PEMANFAATAN SUMBERDAYA LINGKUNGAN GUA GILAP DI KAWASAN KARST WONOGIRI PADA MASA PRASEJARAH: KAJIAN TERHADAP SISA FAUNA - , FALENTINUS TRIWIJAYA ATMOKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Topic This research was done on Gilap Cave, Wonogiri. Genesisly and morphology, this cave was a collapse doline which was made by roof detritus of a basement, which became an ideal habitat for prehistory human because it was supported by the ideal environment and the potential of natural resources around there. Problems 1. How did the utilization of natural resources esspecially the fauna resources arround Gilap cave by the cave inhabitants in the prehistoric time? 2. How did the kind of Gilap cave potentials and the environment as the habitat for prehistory human? Aim : Giving description about the kind of good environment potentials in micro or meso- which could support the prehistory habitat on Gilap cave and the utilization of fauna resources to contribute the substantion. Method This research used exploration method by using induction reasoning. Collecting data was obtained by observation and excavation. The observation was done in field study and literature. The analysis was done by artefactual and ecofactual analysis, contextual analysis and locational analysis. Summary This research had done to identify the kind of potential resources which contributed human habitat in prehostory era. Substantion activities were not only depending on the land fauna hunted, but also aquatic fauna. Besides that, it also created the reconsturction arround the Gilap cave such as savannah and forest-opened